Early adjunctive methylene blue in patients with septic shock: a randomized controlled trial - Miguel Ibarra-Estrada; Eduardo Kattan; Pavel Aguilera-González; Laura Sandoval-Plascencia; Uriel Rico-Jauregui; Carlos A. Gómez-Partida; Iris X. Ortiz-Macías; José A. López-Pulgarín; Quetzalcóatl Chávez-Peña; Julio C. Mijangos-Méndez; Guadalupe Aguirre-Avalos; Glenn Hernández (Critical Care, 2023)
Abstract Purpose Methylene blue (MB) has been tested as a rescue therapy for patients with refractory septic shock. However, there is a lack of evidence on MB as an adjuvant therapy, its’ optimal timing, dosing and safety profile. We aimed to assess whether early adjunctive MB can reduce time to vasopressor discontinuation in patients with septic shock. Methods In this single-center randomized controlled trial, we assigned patients with septic shock according to Sepsis-3 criteria to MB or placebo. Primary outcome was time to vasopressor discontinuation at 28 days. Secondary outcomes included vasopressor-free days at 28 days, days on mechanical ventilator, length of stay in ICU and hospital, and mortality at 28 days. Results Among 91 randomized patients, forty-five were assigned to MB and 46 to placebo. The MB group had a shorter time to vasopressor discontinuation (69 h [IQR 59–83] vs 94 h [IQR 74–141]; p < 0.001), one more day of vasopressor-free days at day 28 (p = 0.008), a shorter ICU length of stay by 1.5 days (p = 0.039) and shorter hospital length of stay by 2.7 days (p = 0.027) compared to patients in the control group. Days on mechanical ventilator and mortality were similar. There were no serious adverse effects related to MB administration. Conclusion In patients with septic shock, MB initiated within 24 h reduced time to vasopressor discontinuation and increased vasopressor-free days at 28 days. It also reduced length of stay in ICU and hospital without adverse effects. Our study supports further research regarding MB in larger randomized clinical trials. Trial registration ClinicalTrials.gov registration number NCT04446871 , June 25, 2020, retrospectively registered.